Automatic selection of lung cancer patients for adaptive radiotherapy using cone-beam CT imaging. (January 2017) - van den Bosch, Michiel; Öllers, Michel; Reymen, Bart; van Elmpt, Wouter
Abstract: Background and purpose: Anatomical changes in non-small cell lung cancer (NSCLC) patients may lead to unacceptable treatment results, requiring adaptive radiotherapy (ART). The method proposed in this study describes the proof-of-principle to automatically select patients eligible for ART. Materials and methods: A method was developed flagging patients potentially requiring replanning using changes in density information between the planning CT and cone-beam CT (CBCT) scan. Potential candidates were defined based on anatomical changes in the primary tumour, mediastinum and a region including the lungs. In total, CBCTs of 70 NSCLC patients were retrospectively scored by two independent experts for the need of replanning using the clinical guidelines. Expert evaluation was used as benchmark for the automatic method and accuracy was quantified using a leave-one-out cross-validation strategy. Results: The automatic method correctly selected 79%, 71%, and 89% of the pre-defined candidates based on anatomical change in the tumour, mediastinum and lungs, respectively. The false positive rate was 27%, 9%, and 19% for these regions, respectively. If a single criterion ('flag') per patient is sufficient for replanning, the overall sensitivity was 89% with a false positive rate of 34%. Most common reasons for false positives were changes in breathing pattern or anatomical shifts outside the evaluated region. Excluding these reasons, the false positive rate dropped to 21% and the accuracy was almost similar to expert evaluation: overall sensitivity of approx. 95% with a false positive rate below 19%. Conclusion: Our method based on daily CBCT allows automatic selection of patients that should be investigated for treatment adaptation.